Zinc supplementation on cellular immune response in splenectomized thalassemia major - Sari, Teny Tjitra; Gatot, Djajadiman; Akib, Arwin AP; Waspadji, Sarwono; Hadinegoro, Sri Rezeki S; Harahap, Alida Roswita; Idjradinata, Ponpon S (Paediatrica Indonesiana, 2024)
Background: The immune response of thalassemia patients is different from usual; therefore, thalassemia patients are susceptible to infection. A study at Thalassemia Center in Cipto Mangunkusumo Hospital showed that all thalassemia patients experience zinc deficiency. The decreased cellular immune response is associated with zinc deficiency, whereas splenectomy exacerbates the condition. This study aims to evaluate the improvement of cellular immune response in splenectomized thalassemia major patients after zinc supplementation. Method: Randomized double-blinded controlled trial was conducted on splenectomized thalassemia major patients in 12 weeks period. The inclusion criteria were aged > 12 years and had negative HIV test results. The subject receiving corticosteroids were excluded. Fifty-six subjects were randomly divided into two groups, the zinc group and the placebo group. Between 2 groups, data on zinc serum, T lymphocyte count, CD4+ T lymphocyte count, CD8+ T lymphocyte count, and CD4+/CD8+ ratio were evaluated at the beginning and the end of the study and were analyzed with unpaired t-test, Mann Whitney test, and Wilcoxon Signed Rank test. Result: After zinc supplementation, only 18 of 28 subjects in the zinc group recovered normal zinc serum levels. There were no significant changes after zinc supplementation in all parameters of cellular immune response (p > 0.05) between the two groups. This might be due to the subjects' adherence, which was lower in the zinc group (75.82%) than in the placebo group (83.19%). Conclusion: The effect of zinc supplementation on cellular immune response in splenectomized thalassemia major patients had not been proven yet.